Autonomous Ultrafast Self‐Healing Hydrogels by pH‐Responsive Functional Nanofiber Gelators as Cell Matrices. Issue 2 (9th November 2018) - Gačanin, Jasmina; Hedrich, Jana; Sieste, Stefanie; Glaßer, Gunnar; Lieberwirth, Ingo; Schilling, Corinna; Fischer, Stephan; Barth, Holger; Knöll, Bernd; Synatschke, Christopher V.; Weil, Tanja
Abstract: The synthesis of hybrid hydrogels by pH‐controlled structural transition with exceptional rheological properties as cellular matrix is reported. "Depsi" peptide sequences are grafted onto a polypeptide backbone that undergo a pH‐induced intramolecular O–N–acyl migration at physiological conditions affording peptide nanofibers (PNFs) as supramolecular gelators. The polypeptide–PNF hydrogels are mechanically remarkably robust. They reveal exciting thixotropic behavior with immediate in situ recovery after exposure to various high strains over long periods and self‐repair of defects by instantaneous reassembly. High cytocompatibility, convenient functionalization by coassembly, and controlled enzymatic degradation but stability in 2D and 3D cell culture as demonstrated by the encapsulation of primary human umbilical vein endothelial cells and neuronal cells open many attractive opportunities for 3D tissue engineering and other biomedical applications. Abstract : Tissue engineering requires biocompatible, dynamic materials mimicking the extracellular matrix. Hybrid hydrogels from albumin‐derived copolymers grafted with functional peptide nanofiber gelators are developed. pH‐induced intramolecular rearrangement of peptide grafts facilitates gelation at physiological conditions, providing injectability and excellent biocompatibility for primary cells. The mechanically robust hybrids feature ultrafast autonomous self‐recovery and show promise in biomedical applications.